Towards Substantive Justice: Reforming Islamic Family Law Regarding the Division of Marital Property in Indonesia - Muhammad Nawawi; Ansari Ansari; Arifuddin Muda Harahap (Hukum Keluarga Islam IAIN LANGSA, 2025)
The division of marital property in marriage constitutes a complex issue within Islamic family law in Indonesia. The Compilation of Islamic Law (KHI) stipulates that, in the event of divorce, both former spouses are each entitled to 50% of the marital property. However, the principle of justice is not merely determined by numerical equality but also by considering each party’s contribution and socio-economic circumstances. This study focuses on formulating an ideal legal framework for the regulation of marital property in Indonesia to ensure justice for all parties involved. The primary aim of this research is to propose a legal model for the division of marital property that is more adaptive to social realities and capable of ensuring substantive justice. The study adopts Werner Menski’s triangular concept of legal pluralism, integrating normative, empirical, and philosophical approaches. It employs a qualitative method, combining library research with in-depth interviews with religious court judges. The findings reveal that although the KHI prescribes an equal division of marital property, in practice judges may exercise their ex officio authority to adjust rulings in order to achieve fairness. An ideal regulation should not rely solely on formal equality but must also take into account the actual contributions of each party in acquiring the marital property. A progressive legal approach is necessary for Islamic family law to become more responsive to societal developments and to guarantee substantive justice for the parties concerned.